New Methods in the Psychology of Religion - Malony, H. Newton (Journal of psychology and theology, 1976)
Preferred assumptions for the study of religion by psychologists are noted. They are religious empathy, grounding in general psychology, and experimental methodology. Possible new approaches to the psychological study of religion are discussed as they related to (1) theory (cf. cognitive dissonance and experiencing); (2) subjects (secular religionists and encounter group participants); (3) techniques (game theory and obedience to authority); and (4) dependent measures (religiosity and value conflict).